QUANTITATIVE APPROACH TO INFLUENCING DRIVERS FOR SUSTAINABLE AGRICULTURE DEVELOPMENT - Vili DRAGOMIR; Bianca BOLBOASA; Steliana RODINO; Marian BUTU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The need to address the complex exchanges between natural resource efficiency and economic growth has become increasingly discussed in worldwide strategies and position papers. Resource depletion, environmental challenges and climate change are just a few topics related to fast industrialization and economic expansion. The question is how information regarding crops, climatic factors, or solutions used in plant treatment are managed. The purpose of this paper is to provide an overview of the scientific environment regarding quantitative indicators and models for the assessment of sustainable agriculture practices. The study is based on a bibliometric analysis made using Web of science database and processing using biblioshiny environment from R package. The most relevant works and influential authors in the field of quantitative modelling for sustainable agriculture were identified and a set of indicators and metrics for evaluating efforts in transitioning towards sustainability were synthetised. Integrating practical data into quantitative models can provide insights into trends, correlations, or even predictions, and the results obtained serve as inputs for decision-makers.